THE USE OF ICTs AND ITS RELATION WITH THE COMPETITIVENESS OF MEXICAN SMEs - Cuevas-Vargas, Héctor; Enríquez, Luis Aguilera; Adame, Martha González; Servin, Joe Luis (European Scientific Journal, ESJ, 2015)
This empirical study was aimed to analyze the relationship between the use of Information and Communication Technologies (ICT) and the competitiveness of manufacturing Small and Medium Enterprises (SME) in the state of Aguascalientes, Mexico, using size and age of the company as control variables. The scales in which the use of ICT and competitiveness were measured, were subjected to a first Order confirmatory factor analysis (CFA), through the Method of Maximum Likelihood, for which they have reliability and convergent and discriminant validity. When the survey was applied to managers or owners of 200 manufacturing SMEs, the results obtained through linear regression analysis by Ordinary Least Squares (OLS) under the stepwise method, allowed to infer that ICTs have a positive and highly significant relationship with the competitiveness of these types of businesses, finding no evidence that the size or age of these types of businesses influence over the impact on the competitiveness using ICT.